Management of Gastric Varices - Lusy Erawati; Marcellus Simadibrata; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2004)
Upper gastrointestinal bleeding is one of the emergency conditions in the field of gastroenterology and variceal bleeding is the most common cause of it. Gastric varices accounts only 5% to 10% of all causes of upper gastrointestinal bleeding respectively, but it could be fatal and difficult to control despite provision of adequate therapy. Early diagnosis and appropriate management may decrease the morbidity and mortality of gastric variceal bleeding. Keywords: Gastric varices, upper gastrointestinal bleeding, endoscopy